111 Carbon and blue water footprints of California sheep production. (7th December 2018) - Dougherty, H; Oltjen, J; Mitloehner, F; DePeters, E; Pettey, L; Macon, D; Finzel, J; Rodrigues, K; Kebreab, E
Abstract: While the environmental impacts of livestock production have been studied for a variety of livestock production systems, information is still lacking for US sheep production. A cradle-to-farm gate life cycle assessment was conducted according to international standards (ISO 14040/44), analyzing the impacts of five different meat sheep production systems in California, and focusing on carbon footprint (carbon dioxide equivalents, CO2 e) and irrigated water usage (MT). This study is the first to look at the carbon footprint of the California sheep industry and to consider both wool and meat production across the diverse sheep production systems within California. This study also explicitly examined the carbon footprint of hair sheep as compared with wooled sheep production. Data were derived from producer interviews and literature values, and California-specific emission factors were used wherever possible. The carbon footprint of market lamb production ranged from 13.9 to 30.6 kg CO2 e/kg market lamb production on a mass basis, 10.4 to 18.1 on an economic basis, and 6.59 to 10.1 on a protein mass basis. Whole-ranch water usage ranged from 2.06 to 44.8 MT/kg market lamb, almost entirely from feed production, and four of five case studies used irrigated pasture for at least part of the year. Enteric methane (CH4 ) production was the largest single source of emissions for all case studies, averaging 72% of total emissions. Emissions from manure credited to feed or from feed production averaged 22% in total. Sensitivity analysis showed that carbon footprint per kg market lamb increased as ewe replacement rate increased and decreased as lambs born/ewe bred increased. These results provide a proactive benchmark for the previously-unknown environmental impacts of current sheep production systems in California, which could be used to spur research into other US sheep production systems.